We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
251
1
avatar

n

4

37

an

45

606

Hint: an = a1 + d(n − 1), where a1 is the first term and d is the common difference.

 

Part A: What is the first term, a1, of the sequence?

 

Part B: What is the general term equation, an, for this sequence?

 

Part C: What is the value of the 13th term of this sequence?

 Feb 27, 2018
 #1
avatar+100571 
0

a4  = 37

a45 = 606

 

We have  45 - 4  = 41 terms between these

 

So.....d  =

 

[606 - 37 ] / 41   = 569 / 41

 

The first term is

 

37 - 3(569/41)  =   -190/41

 

The general equation  is

 

an  =   -190/41   + (569/41(n - 1)

 

The 13th term is

 

a13  =  6638 / 41

 

 

 

cool cool cool

 Feb 27, 2018

4 Online Users